2018
DOI: 10.1016/j.cct.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to prevent excessive gestational weight gain and promote postpartum weight loss in overweight and obese women: Health In Pregnancy and Postpartum (HIPP)

Abstract: HIPP is an innovative study that addresses significant gaps in the literature. Primary outcome results are expected in 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 90 publications
0
28
0
1
Order By: Relevance
“…One approach was through psychoeducation. For example, pregnant and postpartum women obtained health information, identified risk behaviors and situations, learned to set achievable goals, and used behavior skills [28,29]. Thus, the participants were expected to manage their weight or control glucose by increasing their physical activity and changing dietary intake [27,30-32].…”
Section: Resultsmentioning
confidence: 99%
“…One approach was through psychoeducation. For example, pregnant and postpartum women obtained health information, identified risk behaviors and situations, learned to set achievable goals, and used behavior skills [28,29]. Thus, the participants were expected to manage their weight or control glucose by increasing their physical activity and changing dietary intake [27,30-32].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with best practices [66], our approach will include multiple strategies, ranging from monetary reimbursement to orientation sessions conducted prior to randomization [69]. To our knowledge, GLOW is one of only two trials to implement the MMI orientation session approach among pregnant women [76].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 illustrates a different input-output model structure for urban and rural area data. Nevertheless, some limitations of the current study are as follows: In previous studies, the parity of mothers [ 86 ] was found to be one of the factors that lead to postpartum obesity and should be included in a model. Therefore, the suggestion to study this factor in future research on account of its significance is proposed.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, the parity of mothers [ 86 ] was found to be one of the factors that lead to postpartum obesity and should be included in a model. Therefore, the suggestion to study this factor in future research on account of its significance is proposed.…”
Section: Discussionmentioning
confidence: 99%